Analisis Minat Beli Sepeda Listrik Selis dengan Pendekatan Technology Acceptance Model (TAM) di Yogyakarta - Arif Sudaryan; Tarisa Septi Wandari; Anindita Imam Basri (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the interest in buying Selis electric bicycles using the Technology Acceptance Model (TAM) approach in Yogyakarta. This study is a quantitative study using data analysis, namely multiple linear regression analysis processed using the assistance of the IBM SPSS version 26 program calculation. The population of this study is consumers who have purchased or have not purchased Selis electric bicycles in Yogyakarta as many as 100 respondents with a purposive sampling technique. The results of this study indicate that the variables partially perceived usefulness and trust have a positive and significant effect on the purchase interest of Selis electric bicycles in Yogyakarta, while perceived ease of use and perceived security have a positive but insignificant effect on the purchase interest of Selis electric bicycles in Yogyakarta. The results of the F test indicate that the variables of perceived usefulness, perceived ease of use, perceived security, and trust together or simultaneously have a positive and significant effect on the purchase interest of Selis electric bicycles in Yogyakarta. The variables of perceived usefulness, perceived ease of use, perceived security, and trust are able to explain the purchase interest variable by 52.5%, while the remaining 47.5% is influenced by other factors not examined in this study.